(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2014)
Acetylcholinesterase (AChE) from Caridina sp. was tested its sensitivity towards selected anticholinesterase such as malathion. Prior to this study, the optimal assay condition was determined at the temperature of 25oC, pH 8.0 and using phosphate buffer. At the concentration of 10-8 M, malathion was able to inhibit AChE activity at 1.75% and increased to 15.79% with the increasing of malathion concentration to 10-4 M. It is proven through this study that the crude extract of AChE is sensitive toward malathion exposure and provide an alternative study for biosensor development.